Analisis Penggunaan Terjemah Arab Pegon dalam Pembelajaran Nahwu Kitab Matan Al Jurumiyah Pondok Pesantren Insan Mulia Punggur Lampung Tengah - Roidah, Salma; Izzah, Nailul; Munawaroh, Lailatul (CV. Creative Tugu Pena, 2024)
This article analyzes the use of Pegon Arabic in learning the Nahwu Matan al Jurumiyah book at the Insan Mulia Punggur Islamic boarding school, Central Lampung. The purpose of this library research is to find out more about the use, problems, advantages and disadvantages of learning the Nahwu Matan al-Jurumiyah book. This study uses a qualitative method with a phenomenological approach. Phenomenology uses life experiences as basic data from reality. In this qualitative study, researchers use more research questions to provide direction to researchers regarding the symptoms or phenomena of several problem themes. The objects of this study are all students of class VII of the Insan Mulia Punggur Islamic Boarding School. The data for this study comes from teaching and learning activities in class VII of the Insan Mulia Islamic Boarding School and several teachers who work there. This study uses data collection techniques, namely interviews and observations. The results of this study are that the use of Pegon Arabic as a translator of the Matan al Jurumiyah book has an important role in learning Nahwu in Islamic boarding schools, although it is necessary to develop learning methods to overcome obstacles in learning Nahwu and an appropriate approach is needed to improve students' understanding in studying the Nahwu Matan al Jurumiyah book. It is hoped that subsequent researchers can emphasize more on other aspects such as media in studying the Nahwu Matan al Jurumiyah book.